2022
DOI: 10.3389/fnagi.2022.799732
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Brain Function in Patients With Cognitive Impairment Based on fNIRS and Gait Analysis

Abstract: BackgroundEarly detection of mild cognitive impairment is crucial in the prevention of Alzheimer’s disease (AD). This study aims to explore the changes in gait and brain co-functional connectivity between cognitively healthy and cognitively impaired groups under dual-task walking through the functional near-infrared spectroscopy (fNIRS) and gait analysis devices.MethodThis study used fNIRS device and gait analysis devices to collect the data of 54 older adults. According to the Mini-mental State Examination (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Eventually, 13 studies were included in this systematic review and meta‐analysis. Among them, 13 studies were included in the qualitative synthesis (Bu et al., 2019 ; Ghafoor et al., 2019 ; Li et al., 2019 ; Liu et al., 2021 ; Nguyen et al., 2019 ; Niu et al., 2019 ; Tang & Chan, 2018 ; Wang et al., 2022 ; Yang & Hong, 2021 ; Yoo & Hong, 2019a , 2019 b ; Yu et al., 2020 ; Zhang et al., 2022 ), whereas only 2 studies met the criteria for quantitative synthesis (Bu et al., 2019 ; Zhang et al., 2022 ). The PRISMA flow diagram of the literature search and study selection strategy is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eventually, 13 studies were included in this systematic review and meta‐analysis. Among them, 13 studies were included in the qualitative synthesis (Bu et al., 2019 ; Ghafoor et al., 2019 ; Li et al., 2019 ; Liu et al., 2021 ; Nguyen et al., 2019 ; Niu et al., 2019 ; Tang & Chan, 2018 ; Wang et al., 2022 ; Yang & Hong, 2021 ; Yoo & Hong, 2019a , 2019 b ; Yu et al., 2020 ; Zhang et al., 2022 ), whereas only 2 studies met the criteria for quantitative synthesis (Bu et al., 2019 ; Zhang et al., 2022 ). The PRISMA flow diagram of the literature search and study selection strategy is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Dual‐task paradigms have gain increased popularity in brain studies, providing a gold standard for evaluating the “central executive system” (Bishnoi et al., 2021 ). Studies investigating FC during dual‐task walking have shown mixed findings, revealing both increased and reduced prefrontal‐related connectivity (Liu et al., 2021 ; Wang et al., 2022 ). These inconsistencies might be attributed to task differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Niu and colleagues assessed participants with amnestic MCI and HC during a resting state and reported disrupted dynamic brain connectivity with increased variability in those with MCI [ 44 ]. Finally, Wang and colleagues examined individuals with MCI and HC during walking tasks [ 45 ]. Although no differences were detected during the walking-only tasks, connection strength was greater in the HC than in the MCI patients during more difficult dual task (more complex cognitive activities elicited greater differences).…”
Section: Resultsmentioning
confidence: 99%
“…Although individuals with MCI can typically perform daily activities independently, they may encounter difficulties in performing more complex tasks such as handling banking matters [1][2][3]. MCI frequently results in gait disorders, given that physical functionality, motor accuracy, balance, and spatial cognition are generally lower than those in healthy older adults [4]. This decline can pose challenges for individuals with MCI in maintaining stability or responding to questions while walking, thereby increasing the risk of falls and unstable posture [5,6].…”
Section: Introductionmentioning
confidence: 99%